Magnetic resonance imaging in heart failure, including coronary imaging: numbers, facts, and challenges. (21st November 2017) - Adams, Lisa; Noutsias, Michel; Bigalke, Boris; Makowski, Marcus R.
Abstract: Coronary artery disease (CAD) is a major risk factor for the incidence and progression of heart failure (HF). HF is characterized by a substantial morbidity and mortality and its lifetime risk is estimated at approximately 20% for men and women. As patients are in most cases identified only after developing overt clinical symptoms, detecting early stages of CAD and HF is of paramount importance. Due to its non‐invasiveness, excellent soft‐tissue contrast, high spatial resolution, and multiparametric nature, cardiovascular magnetic resonance (CMR) imaging has emerged as a promising radiation‐free technique to assess a wide range of cardiovascular diseases such as CAD or HF, enabling a comprehensive evaluation of myocardial anatomy, regional and global function, and viability with the additional benefit of in vivo tissue characterization. CMR has the potential to enhance our understanding of coronary atherosclerosis and the aetiology of HF on functional and biological levels, to identify patients at risk for CAD or HF, and to enable individualized patient management and improved outcomes. Even though larger‐scale studies on the different applications of CMR for the assessment of heart failure are scarce, recent research highlighted new possible clinical applications for CMR in the evaluation of CAD and HF.